SUSTAINABILITY: WHAT ARE WE LOOKING FOR? - EDITORIAL - Carniatto, Irene (International Journal of Environmental Resilience Research and Science, 2020)
Sustainability is a very widespread concept in recent decades, with growing interest among academic researchers. Considering the environmental imbalance and the climatic changes caused by the predatory action of man, its study gains a configuration of great relevance in face of the planetary emergency. The term has been discussed by renowned authors such as Caride & Meira, 2004; Fien & Tilbury, 2002; Freitas, 2000; Garcia & Vergara, 2000; Guerra, 2009; Sachs, 2004; Meira & Sato, 2005, apud Faustino and Amador, 2019, who affirm that the various definitions of Sustainable Development, in line with the Brundtland report, are supported by a highly anthropocentric and deeply economics vision that leads “nature to be seen essentially as a resource, which is perceived as an object that man uses, explores and discards according to his needs and desires for capital accumulation (Bonnett, 2007, p. 3). International organizations, governments, companies, communities, even people and children already refer to the term frequently. But, the question is: What sustainability is each talking about? This is an ever-present challenge that must be pursued through community participation, studies and scientific research that can contribute to shedding light on different sectors or segments where sustainability, quality of life and improvement of living conditions are sought for all, living and non-living beings that make up this universe called “Planet Earth”. In order to contribute to the sustainability debate, this issue was opened by the article COSMOCENA ECOLOGY: AN ECOLOGY OF DIFFERENCES “as part of Political Ecology as an expression of Environmental Ecology, which can be recognized as an Ecology of Differences”, by Pereira and Amaral, who they emphasize that the “socio-environmental pathologies of the modern scientific paradigm, and of the capitalist production mode, revealed insufficiencies both in rationality and in the way of production in managing and preserving life”. The CHALLENGES FOR THE INTERNATIONAL RESEARCH NETWORK IN RESIDENTIAL CLIMATE DEVELOPMENT - RIPEDRC are presented by Carniatto et al who, based on the assessment of the impacts of climate change on the agricultural sector, and also on the countless urban activities, warn that “climate change is a of the great challenges of the 21st century, stressing that its consequences would make world trade and peace unstable”. That in order to face this climate emergency, the RIPEDRC Network presents the need for cooperation between the different countries immediately. And other studies... We invite you to read, publicize and present your research to our journal